STUDY ON THE REPRODUCTION OF "LAYANG DELES" SHORTFTN SCAD (Decapterus macnosoma) IN THE JAVA SEA - Suherman Banon Atmaja; Bambang Sadhotomo (Indonesian Fisheries Research Journal, 2005)
Some reproduction aspects of "layang deles" (Decaperus macrosoma) in the Java Sea were investigated using microscope, gonado somatic index and diameter of eggs for determining the stage of maturity.